A low‐cost, easy‐to‐build, and portable bite‐force transducer for birds. Issue 4 (16th December 2021) - Carril, Julieta; Degrange, Federico J.; De Mendoza, Ricardo S.; Tambussi, Claudia P.
ABSTRACT: Few investigators have examined in vivo bite‐force of birds, likely due, at least in part, to the difficulty in accessing suitable force transducers. We describe a low‐cost, easy‐to‐build, and portable force transducer with the goal of encouraging ornithologists to improve our knowledge of in vivo bite forces of birds. We used a commercial piezo‐resistive force sensor (Tekscan © ) to construct our transducer, and measure the bite forces of captive birds with different beak morphologies, including the following species: Greater Rhea ( Rhea americana ), Black‐chested Buzzard‐Eagle ( Geranoaetus melanoleucus ), King Vulture ( Sarcoramphus papa ), Toco Toucan ( Ramphastos toco ), and Graylag Goose ( Anser anser ). Bite forces ranged from 25.1 N for the Toco Toucan to 109.9 N for the King Vulture. By using the bite forces obtained in our study and those reported for other birds in the literature, a regression analysis was performed, revealing that half of the variation in bite force is explained by allometry, with other factors such as beak morphology likely explaining the remaining variation. Our bite‐force transducer should allow researchers to obtain low‐cost, reliable bite‐force data, which will improve our understanding of the relationship between form and function of the avian cranio‐mandibular complex. RESUMEN: Un transductor de fuerza de mordida para aves de bajo costo, fácil construcción y portátil Pocos investigadores han medido la fuerza de mordida in vivo de aves, principalmente debido a la dificultad para acceder a transductores de fuerza adecuados. Aquí se describe un transductor de fuerza de bajo costo, fácil construcción y portátil con el objetivo de incentivar a ornitólogos/as a incrementar el conocimiento sobre la fuerza de mordida real de las aves. Para la construcción del transductor se usó un sensor piezo‐resistivo (Tekscan©). Se midió la fuerza de mordida de aves en cautiverio y con distintas morfologías de pico, incluyendo al ñandú ( Rhea americana ), al águila mora ( Geranoaetus melanoleucus ), al jote real ( Sarcoramphus papa ), al tucán grande ( Ramphastos toco ) y al ganso doméstico ( Anser anser ). El rango de fuerzas de mordida obtenido fue de entre 25, 1 N para el tucán grande y 109, 9 N para el jote real. Con los valores de fuerza de mordida aquí obtenidos y con aquellos publicados en la bibliografía para otras aves se realizó una regresión que reveló que la mitad de la variación en la fuerza de mordida es explicada por alometría y que otros factores como la morfología del pico probablemente explican la variación restante. El transductor de fuerza de mordida aquí descrito permitirá a los investigadores obtener datos de fuerza de mordida fiables y de manera económica, lo que mejorará nuestra comprensión de la relación entre la forma y la función del complejo cráneo‐mandibular de las aves.